Central Visitor Access System (CVAS) in Data Center / Ahmad Al Ihsan Ahmad Al Jeffry - Ahmad Al Jeffry, Ahmad Al Ihsan (2015)
There are many systems and application has been migrated to the web-based in world nowadays. For the time being, Vads Data Center Department (DCM) manages appointment access to data center is totally using manual approach. A short & simple introduction of Vads DCM, subsidiaries by TM and provide 14 data center in Malaysia. The project is mainly to help Vads Data Center Department (DCM) to manage the appointment access in more proper and systematic ways. The projects wills no longer use current ways of compose an email anymore. All of the appointment access will be transfer to web based application. The objective of this project is to design and develop a system that help the department to manage all of the appointment through web based management application. With this project all of the details and information can be easily manage and save time, cost and energy if want to compare will the old approach. There are several aspect will be implemented to this system for example using username & password and verify Mykad Reader Device. PHP and MySQL will be used as the platform to develop this system. In achieving the objectives of the system mentioned, several major activities are implemented such as planning, analysis system, design, development, implementation & testing and last maintenance. The first activity is planning and analysis system, the purpose of this activity is to gather all the information needs. The second activity is design and development system, this activities referring to process flow, database, web page design and coding. The last activity is to implementation and testing and maintenance, this activity focus on the function, performance and upgrading the system. Finally, with successful of this project, it is hope to provide the better and efficient way to make an appointment access process more reliable and simplest ways and hoped that this system will be used widely in all data center Vads around Malaysia.